Antibody mediated hepatocyte injury in methyl dopa induced hepatotoxicity. Issue 11 (November 1985) - Neuberger, J; Kenna, J G; Nouri Aria, K; Williams, R
Abstract : To investigate the mechanisms underlying the hepatotoxicity induced by methyl dopa, we have examined sera from nine patients with liver damage following the use of the drug for evidence of sensitisation to drug altered liver cell membrane antigens using both immunofluorescence and antibody dependent cell mediated cytotoxicity. Five sera induced significant cytotoxicity to hepatocytes isolated from rabbits pretreated with methyl dopa after exposure to the mixed function oxidase inducer, Arachlor 1254. Sera from 10 patients on methyl dopa but with normal liver function and 32 patients with other drug and viral induced liver damage, gave normal cytotoxicity values. Two of the antibody positive sera gave a specific immunofluorescence pattern at the periphery of human hepatocytes when tested on liver biopsy specimens taken from patients taking methyl dopa. These findings are consistent with the view that immune mechanisms directed against drug associated antigens are involved in severe liver damage from methyl dopa administration and that metabolic activation of the drug is implicated in the generation of drug associated antigen. The need for a combination of immune and metabolic factors may explain the rarity of this condition.